Karakteristik Ideal Semiprima Fuzzy - Abdurahim, Abdurahim; Anas, Andy Sofyan; Negara, Habib Ratu Perwira; Ahmad, Ahmad; Primajati, Gilang (University of Mataram, 2018)
A function is called as an fuzzy prime ideal if every fuzzy ideal of and satisfies caused or and a function is called as an fuzzy semiprime ideal if every fuzzy ideal of which requires caused . The previous research has been studied the ideal characteristics of fuzzy prime. Since not all ideal fuzzy semiprime are ideal fuzzy prime, resulted in some characteristic of fuzzy semiprime ideal do not exist in characteristics of the fuzzy prime ideal. This study examines the characteristics of the fuzzy semiprime ideal along with some examples of those characteristics.